Synthesis and Antifungal Activity of 2-Ketophenyl-3-substituted aryl-1-thiazolidin-4-ones - Vishnu Vats; R. K. Upadhyay; Prathibha Sharma (E-Journal of Chemistry)
A new series of 2-ketophenyl-3-substituted aryl-1- thiazolidin-4-ones were synthesized by cyclocondensation of ketoazomethines and thioglycolic acid. Ketoazomethines were synthesized by condensation of phenyl glyoxal (prepared by partial oxidation of acetophenone) and various para-substituted anilines. Their structures were elucidated by elemental analysis, IR and H1 NMR; they were screened for their antifungal activity against hazardous fungi namely Fusarium Oxysporum, Pythium, Sclerotium and Alternaria brassicola.